The Effect of International Financial Reporting Standars on the Real Earnings Management and Internal Control Structure as a Moderating Variable - Hastuti, Dwi Theresia; Ghozali, Imam; Yuyetta, Etna Nur Afri (International Journal of Economics and Financial Issues, 2016)
Earnings management has become a widely known phenomenon towards managing reported earning in order to fulfill targets. Scott (1997) defines earnings management as a management choice upon accounting policy, or a real activity that affects earnings as such that multiple objectives of the specific earnings reporting can be obtained. The perspective of financial statement contends that a manager uses earnings management to match financial analyst’s forecast with the objective of avoiding perception and negative reaction, which in turn brings impact on stock price. This study aimed to examine the effect of IFRS-based accounting standard on the real earnings management moderated by internal control structure. Samples for the study were manufacture companies listed in the Indonesian Stock Exchange 2010-2014. The study found that adoption of the IFRS-based accounting standard had a positive effect on the real earnings management and good corporate governance proxied by internal control structure weaken the positive effect of the IFRS-based accounting standard adoption on the real earnings management. Keywords: Real Earnings Management, IFRS, Good Corporate Governance, Internal Control Structure. JEL Classifications: F38, M4